DAYA TARIK DESTINASI WISATA ALAM & BUDAYA PADANG FULAN FEHAN KAB. BELU NUSA TENGGARA TIMUR - Rinata, Asfira Rachmad; Widodo, Herru Prasetya; Loe, Mariela Gradiana (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2024)
Abstract: The purpose of this study was to determine the Attraction of Natural Cultural Tourism Destinations in Padang Fulan Fehan. Belu, East Nusa Tenggara by using the concept of destination branding theory by Morgan and Pritchard. The type of research used is descriptive qualitative in order to reveal more deeply the tourist attraction of Padang Fulan Fehan as natural and cultural tourism. The results of the study reveal that to see tourist attractiveness apply five stages of destination branding, namely: (1) market investigation, analysis and strategic recommendations stage by implementing SWOT analysis in the form of strengths, weaknesses, opportunities, and threats (threats) Then, (2) the brand identity development stage only uses the name as the brand identity. Furthermore, (3) the brand launch and introduction stage: communicating the vision through promotion through electronic media, online media, and social media, (4) the brand implementation stage in collaboration with the local community (LMDH) and the government. Meanwhile, (5) monitoring, evaluation, and review stages through social media and monitoring the situation in the field. The attraction of Padang Fulan Fehan in the expanse of savanna meadows and cultural attractions that are displayed at certain moments at traditional eventsKeywords: atractions, branding destination, Padang Fulan Fehan tourism, NTT